Book Review of Exceptional Life Journeys: Stories of Childhood Disorder - Kimbel, Tyler M. (Canadian Journal of Counselling and Psychotherapy, 2012)
Exceptional Life Journeys is a collection of personal, parental, and professional stories about experiences with childhood disorder. Ten childhood disorders are discussed within the book’s four parts: Behaviour Disorders, Emotional Disorders, Developmental and Learning Disorders, and Eating and Health-Related Disorders. The editors employ a strengths-based perspective from the introductory sections to the conclusion and including each chapter in between. Readers of this book are offered a unique opportunity to gain awareness about individual journeys with childhood disorder. The review includes a synopsis of the content presented in the text and a critique of its utility for students, professors, and practitioners.